A pszichiátriai betegek gyógykezelése elrendelésének és bírósági felülvizsgálatának elméleti és gyakorlati kérdései - Kerekes, Szilvia (Debreceni Jogi Műhely, 2016)
We can see that the practice of the judicial inspection is not always in accordance with the legislation. The decisions made during the judicial inspection should be written down and delivered as soon as possible. The patient, the head of the institute and the designated medical doctor must be heard smoothly in all cases. All these questions form essential elements of the legal institution of judicial inspection, and, unfortunately, they are still waiting for legal clarification.